ORGANIZATIONAL AND LEGAL BASIS FOR THE PROTECTION OF PERSONAL LIFE, PERSONAL AND FAMILY SECRETS OF CITIZENS IN UZBEKISTAN - Madiev Fakhriddin Khoshim ugli (Scholar Express Journals, 2022)
The following article analyzes the theoretical and practical essence and importance of privacy. As well as that the author points out main issues in this sphere. Besides that, laws on privacy in the experience of Uzbekistan is iscussed.
Keywords: privacy; constitutional rights to privacy; personal life; personal and family secrets